4-allyl-2-(morpholin-4-ylmethyl)-5-( pyridin-4-yl)2,4-dihydro-3H-1,2,4-triazole-3-thione - Dinçer, M; Özdemir, N; Dege, N; Çetin, A; Cansiz, A; Sekerci, M (Int Union Crystallography, 2005)
In the title compound, C15H19N5OS, the morpholine ring adopts a chair conformation. The mean plane of the pyridine ring makes a dihedral angle of 35.16 (7)degrees with the triazole ring plane.